Political Risks Functioning of Party Organizations in modern Russia - S. A. Tsimbal (Проблемы постсоветского пространства, 2017)
In article is analyzed relevance of an assessment of risk of functioning of political parties. Groups of factors which characterize the studied risks are allocated. Approximate techniques of research of political risks of activity of the party organizations are presented.